‘Great Power Style’ in China’s Economic Diplomacy: A Case Study of China-Portugal Economic Relations - Santoso, Rizal Budi; Muttaqin, Rizqi; Moenardy, Dwi Fauziansyah (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2025)
This article examines how China’s economic diplomacy with Portugal demonstrates its global power strategy as a benign hegemon under the Great Power Style paradigm. The paper traces China’s investment trends in Portugal’s key sectors within the Belt and Road Initiative (BRI) framework including energy, ports, finance, and technology using descriptive qualitative methods and literature analysis. The results show that China is not only seeking economic benefits but also creating organized and non-coercive geopolitical influence. This approach is done by providing global public goods and maintaining stable bilateral relations, thereby enhancing China’s position as a responsible great power. Portugal’s strategic location in the Atlantic and its ties to Africa help make it a key node in the 21st Century Maritime Silk Road. The report finds that China’s economic diplomacy is a key component of a distinct global leadership paradigm that prioritises stability, collaboration, and economic attractiveness over military power. Keywords: China, Economic diplomacy, Great Power Style, Investment, Portugal Artikel ini mengkaji bagaimana diplomasi ekonomi Tiongkok dengan Portugal menunjukkan strategi kekuatan globalnya sebagai hegemon jinak di bawah paradigma Great Power Style. Makalah ini melacak tren investasi Tiongkok di sektor-sektor penting Portugal dalam kerangka Belt and Road Initiative (BRI) termasuk energi, pelabuhan, keuangan, dan teknologi menggunakan metode kualitatif deskriptif dan analisis literatur. Hasilnya menunjukkan bahwa Tiongkok tidak hanya mencari keuntungan ekonomi tetapi juga menciptakan pengaruh geopolitik yang terorganisasi dan tidak memaksa. Pendekatan ini dilakukan dengan menyediakan barang-barang publik global dan menjaga hubungan bilateral yang stabil, sehingga meningkatkan posisi Tiongkok sebagai kekuatan besar yang bertanggung jawab. Lokasi strategis Portugal di Atlantik dan hubungannya dengan Afrika membantu menjadikannya simpul utama dalam Jalur Sutra Maritim Abad ke-21. Laporan tersebut menemukan bahwa diplomasi ekonomi Tiongkok adalah komponen utama dari paradigma kepemimpinan global yang berbeda yang memberikan stabilitas, kolaborasi, dan daya tarik ekonomi prioritas utama di atas kekuatan militer. Kata-kata Kunci: Cina, Diplomasi ekonomi, Great Power Style, Investasi, Portugal